Carbon Nanotubes Synthesized by Catalytic Chemical Vapour Deposition using Fe-Supported Zeolite - Zhao1, Wei; Nam Seo1, Dong; Sung Kim2, Hyun; Tae Kim3, Hyung; Jin Kim1, Ik (Asian Journal of Chemistry, 2011)
Multi-walled carbon nanotubes (MWNTs) were synthesized on Fe-supported zeolite by catalytic chemical vapour deposition (CCVD) using acetylene as the carbon source. Well-shaped zeolite NaX (FAU) octahedral crystals of a size of 15 μm were synthesized hydrothermally in a mother solution with a composition of 3.5 Na2O : Al2O3 : 2.1 SiO2 : 1000 H2O. The effect of the iron content and the reaction time on the synthesis of carbon nanotubes (CNTs) was investigated through transmission electron microscopy (TEM), thermogravimetic analysis (TGA) and Raman spectroscopy. After 1 h reaction, quite a number of CNTs had inner and outer diameters both below 10 nm, which were smaller than those of conventional thick MWNTs. With increasing iron contents in the zeolite, the carbon yield shows a monotonic increasing tendency, reaching 52.9 % when the iron content is up to 6.72 wt. %. In addition, with prolonged reaction time, the inner diameter of the CNTs remained constant while the outer diameter became thicker and thicker, with the carbon yield after the reaction of 3 h reaching 58.2 %. Moreover, the CNTs obtained after much longer reaction time may have a weaker crystallinity.